Perilaku Panic Buying pada masa Pandemi Covid-19: Penggunaan Media Sosial, Pemberitaan Media Digital dan Covid-19 Anxiety. - Bambang Setia Wibowo (CAPITAL: Jurnal Ekonomi dan Manajemen, 2022)
This study aims to examined the effect of use of social media, covid-19 anxiety and digital media news on panic buying behavior. This research used survey design with purposive sampling. This study was conducted on 184 students in Yogyakarta who have social media accounts and have experienced panic buying. Data analysis was performed using Structural Equation Model (SEM) using Analysis Moment Structure (AMOS). This research proves that there is a positive influence on the use of social media, digital media news and covid-19 anxiety on panic buying behavior. There are several findings in this study. First, use of social media has positive influence to the panic buying behavior. Second, digital media news has positive effect to panic buying behavior. third covid-19 anxiety has positive effect to panic buying behavior.